Pengaruh Ekuitas Merek Terhadap Keputusan Pembelian pada Konsumen Produk Kapal Api White Coffee di Kabupaten Brebes - Tika Nur Hidayah; Sugeng Rianto (Universitas Peradaban, 2016)
This study aimed to analyze the effect of brand equity on consumer purchasing decision of Kapal Api White Coffee in Brebes regency. This study examines the elements of brand equity consists of brand awareness, brand association, perceived quality, and brand loyalty by analyzing the influence of the four elements of brand equity on purchasing decision of Kapal Api White Coffee in Brebes regency. Data collection technique in this study uses purposive sampling technique and incidental sampling. Data were collected through questionnaires to 100 respondents of Kapal Api White Coffee in Brebes regency, especially in the area of the Paguyangan and Bumiayu sub-district. Data analysis technique used to answer the hypothesis of this study is multiple linear regression analysis. The results of this study showed that brand loyalty significantly influences purchasing decisions, while the brand awareness, brand association and perception of quality do not significantly influence the purchasing decision. The R Square value is 38.1%. It shows that the effect of brand equity to the purchasing decision can be explained 38.1% by brand loyalty, brand awareness, brand association, and perception of quality, while the rest are influenced by other factors not analyzed in this study.